Analisis Kesulitan Belajar Bahasa Inggris Di Kalangan Mahasiswa Keperawatan - Binta Ihtada (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
English plays an important role in nursing education, both in academic and clinical contexts. Nursing students are required to be able to understand medical terminology, communicate with patients and health workers, and access international scientific literature. This study aims to analyze the difficulties experienced by students of the Bachelor of Nursing Study Program at Bhamada Slawi University in learning English. The study used a qualitative descriptive design involving 197 third-semester students divided into classes A, B, C, and D. Data were collected through learning needs questionnaires and limited interviews. The results showed that students experienced difficulties in six main aspects, namely nursing vocabulary, speaking skills for clinical communication, speaking skills for academic presentations, the ability to read nursing texts, academic writing skills, and the ability to listen to clinical instructions and academic explanations. The findings also showed that the fulfillment of English learning needs was closely related to the application of interactive, interesting, and student-centered learning strategies. Strategies such as role play, clinical simulations, presentation-based assignments, and guided reading were considered effective in increasing the engagement and learning outcomes of nursing students.